Synthesis and antifungal activity of some new pyrido[2,3-d]pyrimidines - Hanafy, Fatin Ismail (European Journal of Chemistry, 2011)
Some new pyrido[2,3-d]pyrimidine derivatives (3a-c) were synthesized from 2-amino-5-cyano-6-methoxy-4-(4-methoxyphenyl)pyridine-3-carboxamide. 7-methoxy-5-(4-methoxy phenyl)-4-oxo-2-phenyl-3,4-dihydropyrido[2,3-d]pyrimidine-6-carbonitrile (3b) and 7-met-hoxy-5-(4-methoxyphenyl)-4-oxo-3,4-dihydropyrido[2,3-d]pyrimidine-6-carbonitrile (3c) are used in synthesizing 7a,b, then 8a,b. 7-methoxy-5-(4-methoxyphenyl)-2-methyl-4-oxo-3,4-dihydropyrido[2,3-d]pyrimidine-6-carbonitrile (3a) and 4-hydrazinyl-7-methoxy-5-(4-methoxyphenyl)pyrido[2,3-d]pyrimidine-6-carbonitrile (8b) were condensed with different carbonyl compounds to produce compounds 4, 5, 6 and 9, 10, 11, 12. 3-Methoxy-1-(4-methoxyphenyl)-6-phenyl-7-hydropyridino[2,3-d]1,2,3,4-tetrazolo[1,5-e]pyrimidine-2-carbo-nitrile (13) was synthesized from 8a or 7a. Condensation of 8b with acetophenone to yield 14, which on further reaction gave 15 then 16. 4-Hydrazinyl-7-methoxy-5-(4-methoxyphenyl)-2-phenylpyrido[2,3-d]pyrimidine-6-carbonitrile (8a) also condensed with 4-amino antipyrine giving 17 then 18. Structures of these compounds have been deduced upon the basis of elemental analysis and spectral data. Significant antifungal activities were observed for some of the synthesized compounds.